Second Life in Education in Turkey: A Methodological Review Research - Karabatak, Songül (My University, 2020)
This study aimed to examine the educational studies methodologically using the Second Lifeapplication in Turkey. In the study conducted with the qualitative research paradigm, the documentreview method was used. The studies were analyzed with descriptive analysis technique. Accordingto the findings, it was revealed that qualitative studies as research philosophy and case studies asresearch design were mostly adopted in the studies. In those studies, undergraduate students as thestudy group and questionnaire and interview techniques as data collection methods were mostlypreferred, and the content analysis technique was used mostly for data analysis. Moreover, in thosestudies, the purposive sampling technique was mostly used. Most of the studies examined reachedtheir aims and most of their results were positive.
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği; Eğitim; Eğitim Araştırmaları; Bilgisayar Bilimleri; Bilgi Sistemleri